2016
DOI: 10.3791/53680
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Magnetic Field-Responsive Hybrid Gelatin Microgels for Controlled Drug Release

Abstract: Magnetically-responsive nano/micro-engineered biomaterials that enable a tightly controlled, on-demand drug delivery have been developed as new types of smart soft devices for biomedical applications. Although a number of magnetically-responsive drug delivery systems have demonstrated efficacies through either in vitro proof of concept studies or in vivo preclinical applications, their use in clinical settings is still limited by their insufficient biocompatibility or biodegradability. Additionally, many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Different temperature and pH responsive microgels based on acrylamide moieties have been reported for controlled drug delivery to target cells. 11,92 Sung et al reported crosslinked gelatin based microgels loaded with P(NIPAM-Am) polymer chain as biocompatible and temperature controlled drug delivery system of bovine serum albumin (BSaN). 11 They investigated the kinetics of release of BSaN from aforementioned microgel system under heating and cooling cycles at 22 and 42 C and reported that more than 60% drug can be released from carrier aer four heating and cooling cycles within 3 hours while only 10% release is obtained at constant temperature of 22 C in the same time.…”
Section: Biomedical Applications Of P(nipam-am) Based Microgelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different temperature and pH responsive microgels based on acrylamide moieties have been reported for controlled drug delivery to target cells. 11,92 Sung et al reported crosslinked gelatin based microgels loaded with P(NIPAM-Am) polymer chain as biocompatible and temperature controlled drug delivery system of bovine serum albumin (BSaN). 11 They investigated the kinetics of release of BSaN from aforementioned microgel system under heating and cooling cycles at 22 and 42 C and reported that more than 60% drug can be released from carrier aer four heating and cooling cycles within 3 hours while only 10% release is obtained at constant temperature of 22 C in the same time.…”
Section: Biomedical Applications Of P(nipam-am) Based Microgelsmentioning
confidence: 99%
“…A rapid delivery of Indomethacin drug from P(NIPAM-Am-HEA) microgel particles with 100% release within just 100 minutes has been reported by Fundueanu et al 16 but this study was carried out in methanol instead of aqueous medium which limits its biomedical practical applications. A lot of many other publications on drug delivery systems based on Nipam and Am are available in scientic literature 75,92,93 but acrylamide unit of such kind of microgels is toxic and its toxicity has not been properly addressed in this literature. The low level biodegradability and biocompatibility makes these microgels less desired systems for targeted drug delivery because its long term storage in body causes cytotoxicity.…”
Section: Biomedical Applications Of P(nipam-am) Based Microgelsmentioning
confidence: 99%
“…Furthermore, a hybrid MG device that combines biodegradability and magnetic field-responsivity has been developed. 150 The efficiency of intracellular delivery of nucleic acids can be significantly enhanced by using magnetic force. Among several in vitro studies, the experiment of Deka et al 152 is an interesting example.…”
Section: Protein Therapeutics and Gene Therapymentioning
confidence: 99%
“…These carriers include both organic and inorganic materials. Some are created from metals, while others are made from polymers [ 3 , 7 , 8 ]. Different approaches have been suggested for steering these TDD vehicles; the use of acoustic radiation force, thermo-electromagnetically reacting bilayer-structured microrobots, octagram-shaped microgrippers, and macrophage-based microrobots have been proposed [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%